THE EFFECTS OF SECTION CAESAREA TO EARLY BREASTFEEDING INITIATION: A SYSTEMATIC REVIEW - Nur Annisa Fauziyah; Helda Helda (Yayasan Aliansi Cendekiawan Indonesia Thailand (Indonesian Scholars' Alliance), 2018)
Background: The early breastfeeding initiation is one of the crusial process for successful in exclusive breastfeeding, unfortunately based on UNICEF, globally only 45% of newborns were put to the breast within the first hours of life. The other condition, nowdays caesarean sections have become increasingly common in both developed and developing countries, research showed that mothers who delivered their baby section caesarea have a higher percentage failure of early breastfeeding initiation than mother with vaginal delivery, from that condition his research aims to analyze effects section caesarea to early breastfeeding initiation. Methods: This study used systematic review based on the Prisma (Preferred Reporting Items for Systematic Reviews & Meta-Analyses) Protocol to identify all the published literature using relevant keywords. The initial screening was conducted by human population, the year of publication (5 years) and free full text, then reading the titles, abstracts than assessed for eligibility founded 6 articles, those studies included in this review after selected using inclusion and exclusion criteria. Inclusion are journal from rearch reported in english, has no accompanying disease or health problem as cardiac disease, cancer, herpes, HIV/AIDS, obesity ect. The baby is normal, baby can drink orally. Exclusion: the articles published less than 2013, after sectio caesarea mother and infant require special therapy. Results: The studies showed there were effects of section caesarea to early breastfeeding initiation, the mothers who birth their babies with caesarea most of them failure to initiate early breastfeeding. Conclusions: The way to Improve the rates of early breastfeeding initiation with giving antenatal breastfeeding education to all mothers especially who known to be having a cesarean section and health care professionals must support. All of the hospitals must apply baby friendly hospital initiative to support success of early breastfeeding initiation